Impact of immune checkpoint inhibitors on the management of locally advanced or metastatic non-small cell lung cancer in real-life practice in patients initiating treatment between 2015 and 2018 in France and Germany - Griesinger, Frank; Pérol, Maurice; Girard, Nicolas; Durand-Zaleski, Isabelle; Zacharias, Stefan; Bosquet, Lise; Jänicke, Martina; Quantin, Xavier; Groth, Annika; Fleitz, Annette; Calleja, Alan; Patel, Sonya; et al. (Lung cancer, 2022)
Objectives - To describe the impact of immune checkpoint inhibitors (ICIs) on treatment patterns and survival outcomes in patients with locally advanced or metastatic non-small cell lung cancer (aNSCLC) in France and Germany. - Materials and Methods - Patients with aNSCLC without known ALK or EGFR mutations receiving first-line (1L) therapy were included from (i) the retrospective Epidemiological-Strategy and Medical Economics Advanced and Metastatic Lung Cancer cohort (ESME-AMLC, France; 2015-2018) and (ii) the prospective Clinical Research platform Into molecular testing, treatment and outcome of non-Small cell lung carcinoma Patients platform (CRISP, Germany; 2016-2018). Analyses were stratified according to histology. Survival outcomes were estimated using Kaplan-Meier methodology and stratified by year of 1L therapy. Data sources were analysed separately. - Results - In ESME-AMLC and CRISP, 8,046 and 2,359 patients were included in the study, respectively. In both countries, approximately 20 % of all patients received pembrolizumab monotherapy as 1L treatment in 2018. In ESME-AMLC, the proportion receiving an ICI over the course of treatment (any line) increased from 42.2 % (2015) to 56.1 % (2018) in patients with squamous histology, and 28.9 % to 51.9 % with non-squamous/other; in CRISP, it increased from 50.6 % (2016) to 65.2 % (2018) with squamous histology, and 40.8 % to 62.7 % with non-squamous/other. Two-year overall survival from 1L initiation was 36.8 % and 25.6 % in the squamous cohorts and 36.5 % and 30.8 % in the non-squamous/other cohorts in ESME-AMLC and CRISP, respectively. No significant change in overall survival was observed over time; however, the follow-up time available was limited in the later years of the analysis. - Conclusion - The results of this joint research from two large clinical databases in France and Germany demonstrate the growing use of ICIs in the management of aNSCLC. Future analyses will allow for the evaluation of the impact of ICIs on long-term survival of patients with aNSCLC.
Gesehen am 16.12.2022